Influence of Organic Fertilizers on the Growth Performance of Eucalyptus torilliana Seedlings in Nasarawa State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study aimed to investigate the influence of organic fertilizers on the growth performance of Eucalyptus torilliana seedlings in Nasarawa, Nigeria. Seeds were sown in germination boxes filled with topsoil. At four weeks after germination, 240 seedlings were randomly selected and transplanted into polythene pots filled with 1000 g of top soil. After two weeks of acclimatization, 5 g and 10 g each of poultry manure and cattle dung and 0 g of control were applied as treatments. The experiment was laid out in a completely random design with four treatments. Each treatment consists of 60 experimental pots. Seedling variables such as plant height, number of leaves, leaf area, collar girth, leave length, and leave width were taken fortnightly. The collected data was subjected to an analysis of variance at p
Keywords: Eucalyptus torilliana; Fertilizer; Seedlings; Forest Plantation